ENHANCING ENGLISH SKILLS: A COMPREHENSIVE GUIDE - Botirov Nuriddin Bahriddinovich,; Zubaydova Nilufar Ne’matullayevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: Improving your English skills can open doors to new opportunities in education, career, and personal growth. Whether you are a native speaker or learning English as a second language, enhancing your language abilities involves a combination of strategies. Here are some effective methods to boost your English skills.